Figure 39 from: Palandačić A, Chai MJ, Shandikov GA, Akkari N, Frade PR, Randolf S, Berg H-M, Mikschi E, Bogutskaya NG (2024) An annotated catalogue of selected historical type specimens, including genetic data, housed in the Natural History Museum Vienna. ZooKeys 1203: 253-323. https://doi.org/10.3897/zookeys.1203.117699 - Palandačić, Anja; Chai, Min J.; Shandikov, Gennadiy A.; Akkari, Nesrine; Frade, Pedro R.; Randolf, Susanne; Berg, Hans-Martin; Mikschi, Ernst; Bogutskaya, Nina G. (Zenodo, 2024)
Figure 39 Acquisition Sheet "1828.XI", record 1828.XI.1. Entry for year 1828 in the acquisition book of the bird collection/NHM Vienna for the specimen of Anser erythropus (here sub Anas albifrons), NMW 20.928 (= syntype of Anser brevirostris "Heckel" C.L. Brehm, 1831).